Hypermetabolic state in the 7-month-old triple transgenic mouse model of Alzheimer's disease and the effect of lipoic acid: a (13)C-NMR study - Sancheti, Harsh (J Cereb Blood Flow Metab, 2014)
Alzheimer's disease (AD) is characterized by age-dependent biochemical, metabolic, and physiologic changes. These age-dependent changes ultimately converge to impair cognitive functions. This study was carried out to examine the metabolic changes by probing glucose and tricarboxylic acid cycle metabolism in a 7-month-old triple transgenic mouse model of AD (3xTg-AD). The effect of lipoic acid, an insulin-mimetic agent, was also investigated to examine its ability in modulating age-dependent metabolic changes. Seven-month-old 3xTg-AD mice were given intravenous infusion of [1-(13)C]glucose followed by an ex vivo (13)C nuclear magnetic resonance to determine the concentrations of (13)C-labeled isotopomers of glutamate, glutamine, aspartate, gamma aminobutyric acid, and N-acetylaspartate. An intravenous infusion of [1-(13)C]glucose+[1,2-(13)C]acetate was given for different periods of time to distinguish neuronal and astrocytic metabolism. Enrichments of glutamate, glutamine, and aspartate were calculated after quantifying the total ((12)C+(13)C) concentrations by high-performance liquid chromatography. A hypermetabolic state was clearly evident in 7-month-old 3xTg-AD mice in contrast to the hypometabolic state reported earlier in 13-month-old mice. Hypermetabolism was evidenced by prominent increase of (13)C labeling and enrichment in the 3xTg-AD mice. Lipoic acid feeding to the hypermetabolic 3xTg-AD mice brought the metabolic parameters to the levels of nonTg mice.